Ethical Imperatives and Legal Frameworks in Standard Precautions Compliance: A Comprehensive Health Law Perspective from Indonesia - Noer Triyanto Rusli (Ekasakti Journal of Law and Justice, 2025)
Standard precautions (SPs) are foundational to infection prevention and control, protecting both healthcare workers and patients from healthcare-associated infections (HAIs) and occupational exposures. Beyond clinical necessity, SP adherence represents a moral obligation grounded in the bioethical principles of autonomy, beneficence, non-maleficence, and justice. Furthermore, it is a strict legal mandate under national and international health laws. In low- and middle-income countries, compliance remains inconsistent due to structural, resource-related, and cultural barriers. This article analyzes SP compliance among nurses at a tertiary hospital in Palembang, Indonesia, through the comprehensive lens of medical law, occupational safety regulations, and bioethics. A normative legal and ethical analysis reveals breaches in all four bioethical principles, especially justice, due to inequitable personal protective equipment (PPE) allocation. This article argues that inadequate SP implementation exposes healthcare institutions to significant legal liability, including claims of medical negligence and violations of occupational health rights under Indonesia's Health Omnibus Law (Law No. 17 of 2023). By integrating comparative legal frameworks and analyzing potential tort liabilities, this article demonstrates that hospitals must embed ethical reasoning into infection control policy, ensure equitable resource distribution, and provide regular ethics-informed training to fulfill their legal duty of care and foster a culture of safety.